ADVERTISING AS ECOGOVERNMENTALITY: ANALYSIS OF AKKUYU NUKLEER CAMPAIGN - (:unkn) unknown (INT ORGANIZATION CENTER ACAD RESEARCH, 2015)
In recent years, companies all around the world directed their concerns towards environmental issues regarding the promotion and sales of their products and services. Such developments have been theoretically debated under the terms green marketing and green advertising in academia, especially in the fields of public relations and advertising. It is certain that the increasing market interest in the green has cultural, political and ideological implications, in addition to the market-oriented interests. In this regard, this paper undertakes a critical discourse analysis of the advertisements by Akkuyu Nukleer,a nuclear power plant company that initiated the construction of Turkey's first nuclear plant. By analyzing the campaign's TV and outdoor advertisements, this paper will argue that the green advertising campaign facilitated by the company provides an example for a peculiar form of ecogovernmentality, a term coined after Michel Foucault's notion of governmentality; in the sense that the discourse of the campaign aims to eliminate the potential threats of the nuclear power plantation and hence regulate the ways in which individuals relate themselves to the environment. An agreement between Russia and Turkey for the construction of a nuclear power plant has been signed at May 2010 and the work began at Mersin's Akkuyu district in 2011. As the public raised critical concerns over the project with an increasing attention, the company responded with an advertising campaign launched at March 2015. As this paper will show, the discourse of the campaign focused on the positive aspects of a nuclear plant project especially in terms of its contribution to the energy production, environment and the overall development of future generations. The discourse of advertisements particularly focus on progress, youth and the future; aiming to persuade the public that what they approach in skeptical manner is actually a project with which their hopes for the future will be guaranteed. Significantly, children appear in advertisements as actors and actresses to draw attention to the contribution that the nuclear power plant will make for the safety of future generations. The advertisement discourse however systematically conceals any potential threats and fears that the nuclear power plant may cause. Moreover, the advertisement discourse is constructed in such a homogeneous way since it presents an ideal imagination of Turkey's nuclear era without any risks. Referring to Foucault's terminology, this paper will point at the power-discourse dynamics by analyzing the ways in which the discourse regarding the nuclear plant project is instrumentalized to provide the public with a certain form of understanding about the nuclear phenomenon; which helps the state and the market to govern the existing power relations. To sum up, this paper will first address the ways in which such a discourse is constructed and then will continue with the deconstruction of meaning production in the advertisements by a critical discourse analysis. This paper will eventually show that advertising as a technology of government provides a legitimate space for powerdiscourse- knowledge dynamics to be exercised via advertising as ecogovernmentality to discursively eliminate the potentialities of an ecological disruption.
Keywords: Advertising; Ecogovernmentality; Michel Foucault; Discourse Analysis; Nuclear Power Plant; SUBJECT